The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5194/acpd-15-26555-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aura OMI observations of regional SO<sub>2</sub> and NO<sub>2</sub> pollution changes from 2005 to 2014

Abstract: Abstract. The Ozone Monitoring Instrument (OMI) onboard NASA's Aura satellite has been providing global observations of the ozone layer and key atmospheric pollutant gases, such as nitrogen dioxide (NO2) and sulfur dioxide (SO2), since October 2004. The data products from the same instrument provide consistent spatial and temporal coverage and permit the study of anthropogenic and natural emissions on local-to-global scales. In this paper we examine changes in SO2 and NO2 over some of the world's most polluted… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
131
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(148 citation statements)
references
References 138 publications
(254 reference statements)
17
131
0
Order By: Relevance
“…The NO 2 column has been used to capture NO x emissions (e.g., Miyazaki et al, 2012;Mijling et al, 2013;Itahashi et al, 2014b;Han et al, 2015;Irie et al, 2016), and the SO 2 column has been used for SO 2 emissions (e.g., Lee et al, 2011;Li et al, 2010) and/or volcanic eruptions (e.g., Brenot et al, 2014). Several studies have indicated the importance of different technologies to control emissions (e.g., Li et al, 2010;Wang et al, 2015;Krotkov et al, 2016;van der A et al, 2017). For example, the ratio of Ozone Monitoring Instrument (OMI)-derived SO 2 / NO 2 was used to determine the effectiveness of the flue-gas desulfurization devices for power plants in China (Li et al, 2010;Wang et al, 2015).…”
Section: Satellite Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NO 2 column has been used to capture NO x emissions (e.g., Miyazaki et al, 2012;Mijling et al, 2013;Itahashi et al, 2014b;Han et al, 2015;Irie et al, 2016), and the SO 2 column has been used for SO 2 emissions (e.g., Lee et al, 2011;Li et al, 2010) and/or volcanic eruptions (e.g., Brenot et al, 2014). Several studies have indicated the importance of different technologies to control emissions (e.g., Li et al, 2010;Wang et al, 2015;Krotkov et al, 2016;van der A et al, 2017). For example, the ratio of Ozone Monitoring Instrument (OMI)-derived SO 2 / NO 2 was used to determine the effectiveness of the flue-gas desulfurization devices for power plants in China (Li et al, 2010;Wang et al, 2015).…”
Section: Satellite Observationsmentioning
confidence: 99%
“…NO x emissions in China have been rising steadily (Kurokawa et al, 2013;Itahashi et al, 2014b), whereas SO 2 emissions in China peaked in [2005][2006] and subsequently declined due to the introduction of flue-gas desulfurization systems in China's 11th Five-Year Plan (2006 (Kurokawa et al, 2013;Itahashi et al, 2012). Recently, it has been reported that NO x emissions in China declined after 2011-2012 (Irie et al, 2016;Xia et al, 2016;Krotkov et al, 2016;van der A et al, 2017). To determine the result of this change, we revisited and updated an analysis of precipitation data in relation to emission variation over East Asia.…”
Section: Introductionmentioning
confidence: 99%
“…This decrease in SO 2 over continents correlates well with CDNC observed over the Pacific (10°-40°N, 110°-150°E) and Atlantic (30°-45°N, 80°-65°W) (Figure 5c,d). Land domains were chosen to match the regions of SO 2 production in China and the US examined in Krotkov et al (2016). As noted in Krotkov et al (2016), the Yangtze River delta, Pearl River delta, and Sichuan Basin contribute the majority of emissions in China, while Pennsylvania and the Ohio River valley contribute strongly to North 30 American emissions.…”
Section: Decadal Trends In Cdnc Driven By Sulfur Fluxesmentioning
confidence: 99%
“…Land domains were chosen to match the regions of SO 2 production in China and the US examined in Krotkov et al (2016). As noted in Krotkov et al (2016), the Yangtze River delta, Pearl River delta, and Sichuan Basin contribute the majority of emissions in China, while Pennsylvania and the Ohio River valley contribute strongly to North 30 American emissions. The averages over land have been selected to capture these regions and agree with previous studies .…”
Section: Decadal Trends In Cdnc Driven By Sulfur Fluxesmentioning
confidence: 99%
“…Many studies on Indian air quality rely on satellite observations as a result of these biases and limited availability of ground-based monitor data across India, including NO 2 from OMI aboard the Aura satellite [Lamsal et al, 2010;Ghude et al, 2013]. Satellite observations from OMI and other instruments have been previously used to evaluate emissions and surface concentrations [Lamsal et al, 2010;Lu and Streets, 2012;Lu et al, 2013;Streets et al, 2013], observe trends in air quality [Lamsal et al, 2013[Lamsal et al, , 2015Duncan et al, 2015;Krotkov et al, 2015], evaluate AOD for dust or anthropogenic pollution [King et al, 2003;Isakov et al, 2007;Zhao et al, 2010], and estimate NO X to VOC ratios in assessing O 3 regimes [Jin and Holloway, 2015]. Limitations of satellite observations include temporal availability (i.e.…”
Section: Satellite Observations For Air Quality Analysismentioning
confidence: 99%